Conservation of 5-HT1A receptor-mediated autoinhibition of serotonin (5-HT) neurons in mice with altered 5-HT homeostasis - Araragi, Naozumi; Mlinar, Boris; Baccini, Gilda; Gutknecht, Lise; Lesch, Klaus-Peter; Corradetti, Renato (Frontiers in Pharmacology, 2013)
Firing activity of serotonin (5-HT) neurons in the dorsal raphe nucleus (DRN) is controlled by inhibitory somatodendritic 5-HT1A autoreceptors. This autoinhibitory mechanism is implicated in the etiology of disorders of emotion regulation, such as anxiety disorders and depression, as well as in the mechanism of antidepressant action. Here, we investigated how persistent alterations in brain 5-HT availability affect autoinhibition in two genetically modified mouse models lacking critical mediators of serotonergic transmission: 5-HT transporter knockout (Sert -/-) and tryptophan hydroxylase-2 knockout (Tph2 -/-) mice. The degree of autoinhibition was assessed by loose-seal cell-attached recording in DRN slices. First, application of the 5-HT1A-selective agonist R(+)-8-hydroxy-2-(di-n-propylamino)tetralin showed mild sensitization and marked desensitization of 5-HT1A receptors in Tph2 -/- mice and Sert -/- mice, respectively. While 5-HT neurons from Tph2 -/- mice did not display autoinhibition in response to L-tryptophan, autoinhibition of these neurons was unaltered in Sert -/- mice despite marked desensitization of their 5-HT1A autoreceptors. When the Tph2-dependent 5-HT synthesis step was bypassed by application of 5-hydroxy-L-tryptophan (5-HTP), neurons from both Tph2 -/- and Sert -/- mice decreased their firing rates at significantly lower concentrations of 5-HTP compared to wildtype controls. Our findings demonstrate that, as opposed to the prevalent view, sensitivity of somatodendritic 5-HT1A receptors does not predict the magnitude of 5-HT neuron autoinhibition. Changes in 5-HT1A receptor sensitivity may rather be seen as an adaptive mechanism to keep autoinhibition functioning in response to extremely altered levels of extracellular 5-HT resulting from targeted inactivation of mediators of serotonergic signaling.